Who watches the watchers?: A law and technology perspective on government and private sector surveillance - Cockfield, Arthur J. (Queen's Law Journal, 2003)
The author raises questions about potential threats to our democratic order that may arise from advancements in surveillance technology. Among the developments that concern him are the increasing power of investigators to conduct surveillance, the enhanced ability of the public and private sectors to share information and the steady growth in the sophistication of surveillance technology. At the same time, there is less scrutiny of surveillance practices by independent bodies. The author argues that these factors are combining to make surveillance of individuals dangerously easy. He warns that this may erode key democratic values, particularly freedom of expression and the right to privacy. The author reviews the 'Personal Information Protection and Electronic Documents Act (PIPEDA)', and concludes that while it is a good first step, it falls short by not adopting the European Union's strict approach to consent. As a result,further measures are needed to ensure that democratic values are adequately preserved, such as stronger laws dictating how government and private agencies collect and store information as well as greater accountability of government to its citizens. In addition, to help ensure such accountability, the author argues that there should be a method of tracking government searches for information. Finally, the author suggests an alternative system under which the personally identifying elements of collected information are removed and stored separately, accessible only upon independently verified grounds.